Optimizing Stakeholder Role in Handling Conflict Between College of Pencak Silat Setia Hati Terate With Setia Hati Winongo - Fikri, Rachman; Noor, Irwan; Mindarti, Lely Indah (JPAS (Journal of Public Administration Studies), 2021)
The regency and City of Madiun became the cultural center of Pencak Silat school. There are 11 schools that are affiliated with IPSI. The eleventh of the school has its own Pencak Silat identity. Different identity of the schools raises conflicts, such as PPSHT with PPSHW. Conflicts often occur when doing the tradition of Suran Agung. The Regency and city Madiun government have made various efforts to implementation of Law No. 7 of 2012 about handling of social conflict but that has not been optimal. The research raised of the problem about how the optimisation pattern of stakeholder role in the handling of conflicts between PPSHT and PPSHW in the Regency and city of Madiun by conducting a perspective mapping of stakeholders involved. This research uses qualitative descriptive methods to focusing on 1) role policy Creator, 2) Coordinator, 3) facilitator, 4) Implementer and 5) accelerators in the handling of conflicts transformed into the development of Madiun tourism The Village of Indonesia Fighter. The results of this study revealed that not yet optimal role of each stakeholder in the handling of conflicts even less do a transformation of conflict into the development of Pencak Silat tourism destination. This is due to the absence of a policy derivative in the form in local regulations and has not yet synergitas the role of stakeholders between the regency government and the city of Madiun. So, there is interesting attraction to fight for the Icon of Pencak Silat and throwing responsibility for the conflicts that occur.